Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Tìm x
a) Ta có: \(16x^2-\left(4x-5\right)^2=15\)
\(\Leftrightarrow16x^2-\left(16x^2-40x+25\right)-15=0\)
\(\Leftrightarrow16x^2-16x^2+40x-25-15=0\)
\(\Leftrightarrow40x-40=0\)
\(\Leftrightarrow40x=40\)
hay x=1
Vậy: x=1
b) Ta có: \(\left(2x+3\right)^2-4\left(x-1\right)\left(x+1\right)=49\)
\(\Leftrightarrow4x^2+12x+9-4\left(x^2-1\right)-49=0\)
\(\Leftrightarrow4x^2+12x+9-4x^2+4-49=0\)
\(\Leftrightarrow12x-36=0\)
\(\Leftrightarrow12x=36\)
hay x=3
Vậy: x=3
d) Ta có: \(2\left(x+1\right)^2-\left(x-3\right)\left(x+3\right)-\left(x-4\right)^2=0\)
\(\Leftrightarrow2\left(x^2+2x+1\right)-\left(x^2-9\right)-\left(x^2-8x+16\right)=0\)
\(\Leftrightarrow2x^2+4x+2-x^2+9-x^2+8x-16=0\)
\(\Leftrightarrow12x-5=0\)
\(\Leftrightarrow12x=5\)
hay \(x=\frac{5}{12}\)
Vậy: \(x=\frac{5}{12}\)
e) Ta có: \(\left(x-5\right)^2-x\left(x-4\right)=9\)
\(\Leftrightarrow x^2-10x+25-x^2+4x-9=0\)
\(\Leftrightarrow-6x+16=0\)
\(\Leftrightarrow6x=16\)
hay \(x=\frac{8}{3}\)
Vậy: \(x=\frac{8}{3}\)
f) Ta có: \(\left(x-5\right)^2-\left(x-4\right)\left(1-x\right)=0\)
\(\Leftrightarrow x^2-10x+25-\left(x-x^2-4+4x\right)=0\)
\(\Leftrightarrow x^2-10x+25-x+x^2+4-4x=0\)
\(\Leftrightarrow2x^2-15x+29=0\)
\(\Leftrightarrow2\left(x^2-\frac{15}{2}x+\frac{29}{2}\right)=0\)
\(\Leftrightarrow x^2-2\cdot x\cdot\frac{15}{4}+\frac{225}{16}+\frac{7}{16}=0\)
\(\Leftrightarrow\left(x-\frac{15}{4}\right)^2+\frac{7}{16}=0\)(vô lý)
Vậy: x∈∅
a) 4(x+2) - 7(2x - 1) + 9(3x - 4)=30
⇔4x+8 - 14x + 7 + 27x - 36 = 30
⇔ 17x = 51
⇔ x = 3
b) 2(5x - 8) - 3(4x - 5) = 4(3x - 4) + 11
⇔ 10x - 16 - 12x + 15 = 12x - 16 + 11
⇔ -14x = -4
⇔ x= \(\frac{2}{7}\)
c) 5x(1 - 2x) - 3x(x + 18) = 0
⇔ 5x - 10x\(^2\) - 3x\(^2\) -54x =0
⇔ -13x\(^2\) -49 x = 0
⇔ -x ( 13x + 49 ) =0
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\13x+49=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=\frac{-49}{13}\end{matrix}\right.\)
d) 5x - 3{4x - 2[4x - 3(5x - 2)]} = 182
⇔ 5x - 3[ 4x - 2( 4x - 15x + 6 ) ]= 182
⇔5x - 3 ( 4x - 8x + 30x - 12 ) = 182
⇔ 5x - 3 ( 26x - 12 ) = 182
⇔ 5x - 78x + 36 = 182
⇔ - 73x = 146
⇔ x = -2
a) \(\left(2x-3\right)^2-\left(2x+5\right)^2=10\)
\(\Leftrightarrow4x^2-12x+9-4x^2-20x-25-10=0\)
\(\Leftrightarrow-32x-26=0\)
\(\Leftrightarrow-32x=26\)
\(\Rightarrow x=-\frac{13}{16}\)
b) \(4\left(x+1\right)^2+\left(2x-1\right)^2+8\left(x-1\right)\left(x+1\right)=11\)
\(\Leftrightarrow4x^2+8x+4+4x^2-4x+1+8x^2-8=0\)
\(\Leftrightarrow16x^2+4x-3=0\)
\(\Leftrightarrow4\left(4x^2+x+\frac{1}{16}\right)-\frac{13}{4}=0\)
\(\Leftrightarrow\left[2\left(2x+\frac{1}{4}\right)\right]^2-\left(\frac{\sqrt{13}}{2}\right)^2=0\)
\(\Leftrightarrow\left(4x+\frac{1}{2}-\frac{\sqrt{13}}{2}\right)\left(4x+\frac{1}{2}+\frac{\sqrt{13}}{2}\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}4x+\frac{1-\sqrt{13}}{2}=0\\4x+\frac{1+\sqrt{13}}{2}=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{\sqrt{13}-1}{8}\\x=\frac{-1-\sqrt{13}}{8}\end{cases}}\)
c) \(\left(x+5\right)^2=45+x^2\)
\(\Leftrightarrow x^2+10x+25-x^2-45=0\)
\(\Leftrightarrow10x-20=0\)
\(\Leftrightarrow10x=20\)
\(\Rightarrow x=2\)
d) \(\left(2x-3\right)^2-\left(2x-1\right)^2=-3\)
\(\Leftrightarrow4x^2-12x+9-4x^2+4x-1+3=0\)
\(\Leftrightarrow-8x+11=0\)
\(\Leftrightarrow-8x=-11\)
\(\Rightarrow x=\frac{11}{8}\)
e) \(\left(x-1\right)^2-\left(5x-3\right)^2=0\)
\(\Leftrightarrow\left(x-1-5x+3\right)\left(x-1+5x-3\right)=0\)
\(\Leftrightarrow\left(-4x+2\right)\left(6x-4\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}-4x+2=0\\6x-4=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{1}{2}\\x=\frac{2}{3}\end{cases}}\)